Morphometric covariation between palatal shape and skeletal pattern in Class II growing subjects. - Paoloni, Valeria; Lione, Roberta; Farisco, Francesca; Halazonetis, Demetrios J; Franchi, Lorenzo; Cozza, Paola (Eur J Orthod, 2017)
Objectives: To evaluate the patterns of covariation between palatal and craniofacial morphology in Class II subjects in the early mixed dentition by means of geometric morphometrics. Methods: A cross-sectional sample of 85 Class II subjects (44 females, 41 males; mean age 8.7 years ± 0.8) was collected retrospectively according to the following inclusion criteria: European ancestry (white), Class II skeletal relationship, Class II division 1 dental relationship, early mixed dentition, and prepubertal skeletal maturation. Pre-treatment digital 3D maxillary dental casts and lateral cephalograms were available. Landmarks and semilandmarks were digitized (239 on the palate and 121 on the cephalogram) and geometric morphometric methods (GMM) were applied. Procrustes analysis and principal component analysis (PCA) were performed to reveal the main patterns of palatal shape and craniofacial skeletal shape variation. Two-block partial least squares analysis (PLS) assessed patterns of covariation between palatal morphology and craniofacial morphology. Results: For the morphology of the palate, the first principal component (PC1) described variation in all three dimensions. For the morphology of the craniofacial complex, PC1 showed shape variation mainly in the vertical direction. Palatal shape and craniofacial shape covaried significantly (RV coefficient: 0.199). PLS1 accounted for more than 64 per cent of total covariation and related divergence of the craniofacial complex to palatal height and width. The more a Class II subject tended towards high-angle divergence, the narrower and higher was the palate. Conclusions: Class II high-angle patients tended to have narrower and higher palates, while Class II low-angle patients were related to wider and more shallow palates.
Keywords: Adolescent; Anatomic Landmarks; Cephalometry; Child; Cross-Sectional Studies; Dental Casting Technique; Dentition, Mixed; Female; Humans; Imaging, Three-Dimensional; Male; Malocclusion, Angle Class II; Maxilla; Palate; principal component analysis; Radiography, Dental, Digital